PERAN KEPEMIMPINAN DIRI TERHADAP PERILAKU KINERJA SUMBER DAYA MANUSIA DALAM PENDIDIKAN DI SDIT ALMANAR KOTA BEKASI - Victorynie, Irnie; Wahyuni, Sri; Iqbal, Muhammad (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Human Resources (HR) in education play a crucial role in the success of educational implementation. The urgency of HR in education arises alongside increasing demands for higher quality education in the era of globalization. Improving human resource (HR) performance is the key to the success of any organization, including in the field of education. At SDIT Al-Manar in Bekasi City, it is important to understand how self-leadership can become a major factor in achieving optimal performance for educators. This study aims to analyze the role of self-leadership in the performance behavior of Human Resources (HR) at SDIT Al-Manar, Bekasi City. In the era of globalization and technological advancements, the demand for quality education is increasing, making HR development in education crucial. This research focuses on how self-leadership possessed by teachers and educational staff can enhance their performance. It is a long-term investment that is vital for improving education quality, analyzing several challenges such as limited budgets, lack of support from leadership, and lack of intrinsic motivation, while offering strategies to address these obstacles. Additionally, the study proposes some concrete solutions to improve HR management in education. This research employs a qualitative method with a case study approach at SDIT Al-Manar. Data were obtained through in-depth interviews, observations, and documentation. The results of the study show that self-leadership plays a significant role in shaping positive performance behavior, as reflected in the improvement of competence, professionalism, and adaptability to changes in the educational environment.